Advances and Comments on Traditional Chinese Medicine Syndrome and Treatment on Pancreatic Cancer - Zhen CHEN (Zhongliu Fangzhi Yanjiu)
The advancements in innovative cancer prevention and treatment strategies have achieved remarkable results in the prevention and treatment of various malignant tumors. However, the increasing trend of incidence and mortality of pancreatic cancer (PC) has not shown a significant turnaround. The clarification of the material basis of traditional Chinese medicine (TCM) syndromes can contribute to the multidisciplinary integrated diagnosis and treatment of PC. Damp-heat syndrome is the core syndrome of patients with PC. It has a crucial material basis of inflammatory microenvironment. Formulas with heat-clearing and dampness-removing efficacies can inhibit malignant phenotypes by remodeling the tumor microenvironment. Conventional therapy plus heat-clearing and dampness-removing formulas can enhance the quality of life of patients with PC and significantly prolong their survival time. The systemic inflammatory response index (SIRI) is closely correlated with cytokine changes underlying damp-heat syndrome, and it can be used to direct PC prognosis assessment. In the future, PC diagnosis and treatment based on SIRI classification could distinguish patient subgroups that are responsive to heat-clearing and dampness-removing therapy. Taking damp-heat syndrome as the core point to explore the whole period of syndrome evolution throughout the course of PC could contribute to syndrome-based TCM precision treatment of PC.